Artificial intelligence in Germany: Employees often unaware they are working with AI-based systems - Oliver Giering; Alexandra Fedorets; Jule Adriaans; Stefan Kirchner (DIW Weekly Report, 2021)
Using a new SOEP-IS data module on digitalization including information on the prevalence of AI use in the workplace, this report shows that the term "artificial intelligence" often remains inscrutable in the day-to-day work of many employees. When asked directly about the use of digital systems with the term "artificial intelligence," around 20 percent of the working respondents in the sample indicate that they use such systems. When asked indirectly-without using the term AI-almost double the share of respondents indicate that they use at least one of these digital systems on a daily basis. Thus, many employees are already working with AI-based systems without knowing it. This suggests that the current debate about job displacement due to AI (substitution) needs to be expanded to include perspectives on collaboration between humans and machines. As of 2021, many employees still complete certain tasks themselves but also receive assistance from AI-based systems. Training should be offered for the workforce to gain knowledge about AI and strengthen their AI-related skills. With these measures, as many people as possible can shape technological progress in Germany and thus benefit from it.
Keywords: O30; C83; 330; digitalisation; artificial intelligence; labor market; work